Blueprint conceptualization for a river basin's digital twin - Pal, Debasish; Marttila, Hannu; Ala-Aho, Pertti; Lotsari, Eliisa; Ronkanen, Anna-Kaisa; Gonzales-Inca, Carlos; Croghan, Danny; Korppoo, Marie; Kämäri, Maria; van Rooijen, Erik; Blåfield, Linnea; Silander, Jari; et al. (IWA PUBLISHING, 2025)
To achieve a good ecological status of water resources, we are exploring new frontiers by envisioning river basin planning through the newly promoted digital twin perspective. In river basin management, a digital twin is an innovative virtual paradigm - a holistic living replica of the river basin achieved by seamless integration of real-time monitoring, historical observations, data analytics, predictive modeling, and high-performance computing within a framework of interoperable software and scalable hardware - leveraging nuanced understanding of complex environmental, social, and economic interactions, discerning uncertainties, and bridging critical knowledge gaps for progressive improvement in system understanding, optimization of operational efficiency, and continuous advancements in decision-making. This perspective paper lays the groundwork in transforming the futuristic vision of a river basin's digital twin into reality. The proposed blueprint outlines the processes for integrating digital twin components, creating dynamic replicas of river basin systems, and conducting virtual what-if analyses. Aligning with digital transformation, this work segments the river basin into distinct systems to effectively manage diverse objectives and ensure adaptability across various river basin types with spatiotemporal scalability. Supporting sustainable management, the digital twin holds immense potential to surpass existing decision-support systems through continuous bi-directional feedback loops with the river basin.